AMBIGUITY IN SOUNDTRACK SONGS LYRIC OF MOANA MOVIE - Unpris Yastanti; Anggun Dwi Setiawati (Wanastra: Jurnal Bahasa dan Sastra, 2018)
The objective of this study is to identify the ambiguity in soundtrack song lyrics of Moana Movie. This study used descriptive method to analyze data. The research data collected from “We Know The Way” lyrics and ‘I’m Moana” by soundtrack songs lyric of Moana movie. The result of this study is indicated that : (1) There are 26 ambiguity, 8 structural ambiguity and 18 lexical ambiguity in “We Know the Way” lyric and in “I’m Moana” lyrics there are 45 ambiguity, consist of 10 structural ambiguity and 35 lexical ambiguity. (2) The meaning of soundtrack songs lyric in Moana movie, “We Know The Way” telling the story of  polynesian tribe which they are a fisherman, also, “I’m Moana” has meaning to describe who is Moana and her spirit when she almost give up to save her island and her people. The ambiguities in soundtrack song lyric’s Moana movie make the audiences more interest to this movie; make more variation style in language. It has good combination with the audio.